2008
DOI: 10.1017/s0265021508003669
|View full text |Cite
|
Sign up to set email alerts
|

The early phase of critical illness is a progressive acidic state due to unmeasured anions

Abstract: Metabolic acidosis by unmeasured anions is a clinically relevant phenomenon, which is correlated with mortality. Progressive metabolic acidosis may be ongoing in the early phase of critical illness despite the absence of acidaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
19
0
7
Order By: Relevance
“…High (preresuscitation) SIG levels at ICU admission are known to be related to the presence of sepsis, as well as renal and hepatic dysfunction, and are also probably a marker of tissue hypoperfusion [16]. Some studies [17,18] found a clear association between high SIG levels and mortality, whereas one study did not [19]. The prognostic significance of high SIG levels during admission is probably more relevant when preresuscitation values are measured [19].…”
Section: Discussionmentioning
confidence: 99%
“…High (preresuscitation) SIG levels at ICU admission are known to be related to the presence of sepsis, as well as renal and hepatic dysfunction, and are also probably a marker of tissue hypoperfusion [16]. Some studies [17,18] found a clear association between high SIG levels and mortality, whereas one study did not [19]. The prognostic significance of high SIG levels during admission is probably more relevant when preresuscitation values are measured [19].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a shift to a more acidic pH decreased cystine uptake, whereas the uptake of glutamate, which does not change its ionic state within this pH range, was hardly affected (16,21,137). The regulation of system x c -by pH might be of pathophysiogical relevance, as many disease states, including critical illness (4,44) and diabetes (279), are associated with both acidosis and oxidative stress. Inhibition of system x c -by lactate in rat cortical astrocytes has been reported (124).…”
mentioning
confidence: 99%
“…[14][15][16] In comparison to standard methods, strong ion measurements are able to detect the presence of unmeasured anions, indicating the presence of metabolic acidosis in critically ill patients. 17 Our data show that for severely burn-injured pediatric patients there is a markedly increased SIG, indicating a metabolic acidosis present on admission. Additionally, patients who did not survive had a higher SIG, indicating an increased level of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 59%